Genetic Variability And Selection Response To Heat Tolerance Through Membrane Thermostability In Spring Wheat (Triticum Aestivum L) - Barma, NCD; Islam, MA; Hakim, MA; Sarker, DKR (Bangladesh Journal of Plant Breeding and Genetics, 2011)
The present investigation was undertaken to study the genetic variability and selection response of heat tolerance measured through membrane thermostability (MTS) in F2 derived F4 and F5 generations of five wheat crosses: Kanchan × Gourab, Gourab × Fang 60, Kanchan × Pavon 76, Gourab × Pavon76 and Fang 60 × Pavon76. Each cross was consisted of 65, 60, 77, 72 and 64 F4 bulks including two parents. The study was conducted both in the field and laboratory of Wheat Research Centre, Dinajpur during 2002-03 and 2003-04. A completely randomized design for laboratory experiment and randomized complete block design for field experiments was followed with three replications. Acquired thermal tolerance through Membrane Thermo-stability assay was performed in controlled environment as per method described by Ibrahim and Quick (2001). Other morpho-physiological traits were measured from field experiment. The crosses Kanchan × Gourab, Kanchan × Pavon 76 and Fang 60 × Pavon76 showed high genetic variability with high population mean for MTS in F4 bulks. These crosses also exhibited high-observed response to selection, realized heritability and heritability in standard unit indicating expected good gain through early generation selection. Direct response to selection for this trait was significant in these crosses in F5 generation. Direct selection for MTS significantly improved biomass, grain yield, thousand grain weight, grain filling rate and canopy temperature depression in crosses Kanchan × Pavon 76, Gourab × Pavon76 and Fang 60 × Pavon76 with few exceptions. Direct selection of MTS also improved chlorophyll retention at 21 days after anthesis in crosses Gourab × Fang 60 and Gourab × Pavon76. Significant intergeneration correlations (F4 vs. F5) were observed for MTS in all five crosses studied indicating possibility of effective improvement of this trait through selection in early generation. Key words: Membrane thermostability; selection response; realized heritability; intergeneration correlation. DOI: http://dx.doi.org/10.3329/bjpbg.v23i2.9320 Bangladesh J. Pl. Breed. Genet., 23(2): 15-22, 2010